Implementasi Pendekatan Saintifik di Lembaga Pendidikan Anak Usia Dini - Izzuddin, Ahmad (MASALIQ, 2022)
The scientific approach is a learning process that is designed in such a way, so that in the learning process students can actively participate. There are five stages in the scientific approach, namely observing, asking questions, gathering information, processing information, and communicating. This study uses qualitative research with direct and indirect field observations in several private kindergartens in Keruak District. Data collection techniques in this study include observation, interviews and documentation. The results of this study indicate that (1) In observing activities, students are expected to be able to ask questions about information that has not been understood even though the language is quite limited due to language skills that are still limited. (2) Children can collect information from activities carried out by students as well as simple experiments with the guidance and direction of educators. (3) Students are stimulated to be able to think logically and systematically to obtain conclusions in the form of knowledge. (4) Students can communicate what students get from the observations they have made. (5) Scientific learning is able to stimulate children's creativity because children are more independent, confident, dare to have opinions, and have high curiosity.